KUAT TEKAN PANEL DINDING BETON RINGAN EXPANDED POLYSTYRENE DENGAN LAPIS LUAR PAPAN KALSIUM SILIKAT - Desi Maryani; Ashar Saputra; Andreas Triwiyono (TEKNISIA, 2019)
The need for housing in Indonesia reaches around 1 million houses per year is the reason behind an increasing demand for building materials. Prefabricated wall panels can be used as alternative building materials that have easy and fast advantages in installation. In addition, the use of precast wall panels will also save labor costs. In this study, expanded polystyrene (EPS) lightweight concrete wall panels were a composite with calcium silicate boards. Furthermore, the unity of these materials are called a sandwich panel. The purpose of this study was to determine the potential use of sandwich panels as structural wall panels in terms of compressive strength. Test specimens were 9 EPS panels measuring 1800x610x75mm; 3 of them were a composite with GRC board, 3 other with GRC board outer layer and bolt connector, and 3 panels without reinforcement. The used calcium silicate board is a trade name of GRC board with a thickness of 4mm. Compressive strength testing is carried out referring to SNI 03-3122-1992 (Fibrous Lightweight Concrete Panel).The test results obtained the compressive strength of PP-T, PGP-T, PGB-T panels in a row of 0.72 MPa, 0.84 MPa, and 1.43 MPa. The pattern of damage to the test object was marked by the release of the outer layer of the GRC board and the wall panel was fractured. It can be concluded that the addition of the GRC board outer layer and bolt connector can increase the compressive strength of the wall panel up to 200%. In contrast, the PP-T, PGP-T, and PGB-T panels do not meet the requirements of SNI 03-3122-1992. The resulted compressive strengths are so low that make the expanded polystyrene concrete panel is not avaiable for bearing wall purpose.